Bird Box: Malorie - Book 2 - Malerman, Josh (New York : Del Rey, 2020)
"Twelve years after Malorie and her children rowed up the river to safety, a blindfold is still the only thing that stands between sanity and madness. One glimpse of the creatures that stalk the world will drive a person to unspeakable violence. There remains no explanation. No solution. All Malorie can do is survive--and impart her fierce will to do so on her children get lazy, she tells them. Don't take off your blindfold. AND DON'T LOOK. But then comes what feels like impossible news. And with it, the first time Malorie has allowed herself to hope. Someone very dear to her, someone she believed dead, may be alive ... Malorie has a harrowing choice to make: to live by the rules of survival that have served her so well, or to venture into the darkness and reach for hope once more"--
Keywords: Mother and child -- Fiction; Dystopias -- Fiction; Blindness -- Fiction; Monsters -- Fiction; Quests (Expeditions) -- Fiction; Horror fiction; Apocalyptic fiction; Thrillers (Fiction)